(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study examines the impact of financial investment and technology adoption on operational efficiency in the pharmaceutical industry, with process innovation as a mediating factor. Operational efficiency is critical for pharmaceutical firms to meet regulatory requirements, reduce costs, and remain competitive in a rapidly evolving market. Drawing on Resource-Based View (RBV) and Dynamic Capabilities Theory, this research investigates how financial resources and technological advancements drive performance improvements when coupled with innovative processes. Using a quantitative research approach, data were collected from 250 professionals in the pharmaceutical industry through a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct and mediated relationships among the variables. The findings reveal that both financial investment and technology adoption significantly enhance operational efficiency, while process innovation plays a pivotal mediating role, amplifying their effects. This highlights the importance of integrating financial strategies, technology adoption, and innovative practices to achieve sustained operational excellence. Future research could explore longitudinal dynamics and extend the findings to other industries.